A post-structuralist inquiry into health and health discourse in the lives of young men aged 11 to 19 in the UK - Mills, Danielle (2020)
Background There is increasing attention on young people’s health amidst concerns about their health related behaviours including diet, substance use, and exercise. Little is known about how young people respond to this increased attention, with young men being particularly absent in this area of research.